Odpowiedzi

2010-03-23T16:01:27+01:00
2x+3y = -12 |:2
-3x-4y = 17

x+1,5y = -6
-3x-4y = 17

x = -6-1,5y
-3(-6-1,5y)-4y = 17

x = -6-1,5y
18+4,5y-4y = 17

x = -6-1,5y
0,5y = -1 |:0,5

x = -6-1,5y
y = -2

x = -6+3 = -3

odpowiedź B
1 5 1
Najlepsza Odpowiedź!
2010-03-23T16:01:57+01:00
2x+3y=-12
-3x-4y=17

A.x=3,y=2
2*3+3*2=12, a więc nie spełnia

B.x=-3,y=-2
2*(-3) + 3*(-2) = -6 -6 = -12
-3*(-3) -4*(-2) = 9 + 8 = 17 spełnia

C.x=2,y=-3
2*2+3*(-3) = 4 - 9 = -13 a wiec nie spełnia

D.x=-6,y=-4
2*(-6) + 3*(-4) = -12 - 12 = -24 a więc nie spełnia

tylko B spełnia układ równań
2010-03-23T16:02:06+01:00
2x+3y=-12 /3
-3x-4y=17 /2
6x+9y=-36
-6x-8y=34
----------------
0x+1y=-2

2x+3*-2=-12
2x-6=-12
2x=-12+6
x=-3
Odpowiedź B